Marketing Management Strategies In Enhancing The Competitiveness Of Smes In The Digital Era In Jakarta - Hadi, Eko Supriyanto (Pasundan Social Science Development, 2025)
The shift to the digital era has significantly impacted the Small and Medium Enterprises (SMEs) sector, particularly in enhancing their competitiveness. In Jakarta, one of Indonesia's largest economic hubs, SMEs face the challenge of adapting to technological advancements and digital marketing trends. This study aims to identify effective marketing management strategies for improving the competitiveness of SMEs in the digital era. The research methodology includes literature review and interviews with SME owners in Jakarta. The findings suggest that SMEs need to leverage various digital platforms, such as social media, e-commerce, and data-driven marketing, to expand market reach and enhance brand awareness. Furthermore, marketing strategies focused on customer experience, product personalization, and the use of digital technologies have proven to offer a competitive advantage. However, challenges related to limited resources and technological capabilities remain barriers for some SMEs. Therefore, training and support from both the government and the private sector are essential to accelerate the adoption of technology and digital marketing among SMEs. The study concludes that with the right digital marketing strategies, SMEs can improve their competitiveness in the increasingly competitive Jakarta market.